Critically evaluated key points on hereditary medullary thyroid carcinoma - Zhang, Daqi; Liang, Nan; Sun, Hui; Frattini, Francesco; Sui, Chengqiu; Yang, Mingyu; Wang, Hongbo; Dionigi, Gianlorenzo (Frontiers in Endocrinology, 2024)
Medullary thyroid carcinoma (MTC) accounts for only 3 % of all thyroid carcinomas: 75 % as sporadic MTC (sMTC) and 25 % as hereditary MTC (hMTC) in the context of multiple endocrine neoplasia type 2 (MEN2). Early diagnosis is possible by determining the tumour marker calcitonin (Ctn) when clarifying nodular goitre and by detecting the mutation in the proto-oncogene RET in the MEN2 families. If the Ctn level is only slightly elevated, up to 30 pg/ml in women and up to 60 pg/ml in men, follow-up checks are advisable. At higher levels, surgery should be considered; at a level of > 100 pg/ml, surgery is always advisable. The treatment of choice is total thyroidectomy, possibly with central lymphadenectomy. In the early stage, cure is possible with adequate surgery; in the late stage, treatment with tyrosine kinase inhibitors is an option. RET A mutation analysis should be performed on all patients with MTC. During follow-up, a biochemical distinction is made between: healed (Ctn not measurably low), biochemically incomplete (Ctn increased without tumour detection) and structural tumour detection (metastases on imaging). After MTC surgery, the following results should be available for classification in follow-up care: (i) histology, Ctn immunohistology if necessary, (ii) classification according to the pTNM scheme, (iii) the result of the RET analysis for categorisation into the hereditary or sporadic variant and (iiii) the postoperative Ctn value. Tumour progression is determined by assessing the Ctn doubling time and the RECIST criteria on imaging. In most cases, "active surveillance" is possible. In the case of progression and symptoms, the following applies: local (palliative surgery, radiotherapy) before systemic (tyrosine kinase inhibitors).